Bilioenteric bypass stricture type II with hepatolithiasis: A case report. (September 2020) - Warsinggih,; Fajar, Amir; Labeda, Ibrahim; Uwuratuw, Julianus Aboyaman; Prihantono,; Faruk, Muhammad
Abstract: Introduction: Secondary hepatolithiasis can occur as a result of bilioenteric stenosis or biliary anastomosis stenosis. The incidence of secondary hepatolithiasis appears to increase with increasing rates of hepatobiliary surgery. Here we report the first reported case of secondary hepatolithiasis. Case presentation: A 57-year-old female patient complaining of jaundice all over the body since two years ago. The jaundice was intermittent and progressive. There was a history of previous bilioenteric bypass hepaticojejunostomy Roux-en-Y due to common bile duct cyst. On investigation, we found obstructive jaundice due to stricture of bilioenteric anastomosis type II after bilioenteric bypass hepaticojejunostomy Roux-en-Y with hepatolithiasis type II LR, according to the Takada classification. We did laparotomy found bilateral hepatic duct dilatation, we make incision and remove multiple stones. And then, we performed choledochoscope and confirm total occlusion of tract to distal common hepatic duct. We performed reconstruction Roux-en-Y hepaticojejunostomy with stenting. During the follow-up period, our patients were disease-free. Conclusion: Stricture of bilioenteric anastomosis were successfully treated by surgical reconstruction Roux-en-Y hepaticojejunostomy and stenting. This management has a good outcome and could be an effective alternative to surgery. Highlights: Secondary hepatolithiasis can occur as a result of bilioenteric stenosis or biliary anastomosis stenosis. Here we report the first reported case of bilioenteric bypass stricture type II with Hepatolithiasis. Combination surgical reconstruction Roux-en-Y hepaticojejunostomy and stenting has a good outcome.